The Effectiveness of the Maher Fluid Intelligence Psycho-Educational Intervention Package on Executive Functions and Cognitive Emotion Regulation in Children with Attention-Deficit/Hyperactivity Disorder (ADHD) - Roghani, Farahnaz; Seadatee Shamir, Aboutaleb; Abdollahpour, Mohammad Azad; Hashemi, Nezam (Mental Health and Lifestyle Journal, 2024)
The aim of this study was to determine the effectiveness of the Maher Fluid Intelligence Psycho-Educational Intervention Package on executive functions and cognitive emotion regulation in children with Attention-Deficit/Hyperactivity Disorder (ADHD). The research design was a quasi-experimental pretest-posttest with a control group. The statistical population included all 10–12-year-old boys with ADHD who visited specialized child counseling and psychological service centers in Tehran during the first half of 2023. Based on the research objective, 30 participants were selected from the above population through multistage cluster sampling and were randomly assigned into two groups of 15 (experimental and control). Data collection instruments included the Conners' Parent Rating Scale–Revised: Short Form (CPRS-R:S), the Structured Clinical Interview, the Barkley Deficits in Executive Functioning Scale–Children and Adolescents (BDEFS-CA), and the Cognitive Emotion Regulation Questionnaire–Kids–Parent Version (CERQ-K-P). After conducting the pretest, the control group remained on a waiting list, while the Maher Fluid Intelligence Psycho-Educational Intervention was administered to the experimental group in ten 45-minute group sessions. Research data were analyzed using Multivariate Analysis of Covariance (MANCOVA) and one-way ANCOVA within the MANCOVA framework. The results showed that, following the intervention, there was a significant difference between the experimental and control groups in the increased use of adaptive cognitive emotion regulation strategies, specifically positive refocusing and refocus on planning, as well as in the decreased use of maladaptive cognitive emotion regulation strategies and improvement in executive functions (p < .05). However, no significant differences were found between the groups regarding the adaptive strategies of acceptance, positive reappraisal, and putting into perspective (p > .05). These findings suggest that the Maher Fluid Intelligence Psycho-Educational Intervention Package helps children modulate their emotions, enhances their attention and concentration, and improves their emotional adjustment through deeper comprehension of emotional situations.